Perbedaan Efektivitas Aromaterapi Lemon dan Jahe Untuk Mengurangi Mual Muntah Pada Ibu Hamil Trimester 1 Di Puskesmas Batujajar Tahun 2023 - Maria Awaldina Dua Barbara; Riana Sari Impuh (Jurnal Kesehatan Rajawali, 2023)
Nausea and vomiting must be overcome immediately because it can affect social activities in pregnant women, especially in the first trimester of pregnant women. Efforts were made using non-pharmacological methods by administering lemon aromatherapy and ginger aromatherapy because these methods are more effective in reducing nausea and vomiting. The purpose of this study was to determine the difference in the effectiveness of giving lemon aromatherapy and ginger aromatherapy to reduce the frequency of nausea and vomiting in first-trimester pregnant women. The research design used was a quasi-experimental two-group pre-test post-test design. The research sample was 30 pregnant women with a total sampling technique. The results showed that the Man Whitney Test obtained a p-value = 0.369 (> 0.05), and the results of the statistical test showed that there was no significant difference between giving lemon aromatherapy and ginger aromatherapy to reducing the frequency of nausea and vomiting in the first-trimester pregnant women. The conclusions obtained are that there is no difference in the effectiveness of giving lemon aromatherapy and ginger aromatherapy to reduce the frequency of nausea and vomiting in first-trimester pregnant women. However, giving lemon aromatherapy is more effective than giving ginger aromatherapy in reducing the frequency of nausea and vomiting. Advice that can be given to health workers to increase knowledge about administering lemon aromatherapy and ginger aromatherapy to reduce the frequency of nausea and vomiting in first-trimester pregnant women